THE ROLE OF AMIR TEMUR'S ACTIVITIES IN SPIRITUAL DEVELOPMENT OF YOUTH (Scientific journal of the Fergana State University, 2023)
In this article, state administration during the reign of Amir Temur and information about the structure of the army. In addition, the significance of the scientific legacy that Amir Temur carried out during his career and its importance in shaping the consciousness of young people is highlighted. Also in the article, Amir Temur's activity in the development of New Uzbekistan and the contents of the reforms carried out to inculcate his legacy in the hearts of the youth are analyzed.